Nitrogen fixation during decomposition of sugarcane (Saccharum officinarum) is an important contribution to nutrient supply in traditional dryland agricultural systems of Hawai'i. Issue 2 (2nd April 2016) - Lincoln, Noa Kekuewa; Vitousek, Peter
Abstract : Nitrogen (N) is unique among essential elements required for life, in that it must be fixed from the vast atmospheric reservoir before most organisms can use it. Prior to industrial nitrogen fixation, many agricultural systems were limited in their productivity by N. What sustained N in the ancient Hawaiian dryland (rain-fed) agricultural systems that lacked legumes or other known significant N inputs? N-fixation during sugarcane ( Saccharum officinarum ) growth and litter decomposition was examined in settings representing pre-European Hawaiian agriculture. We did not detect associative N-fixation during the growth of five Hawaiian sugarcane cultivars. In contrast, N-fixation during the decomposition of leaf and stalk material was important. We found that the depth of the mulch layer significantly affected N-fixation levels during decomposition; values of N-fixation in different depths of senesced leaf litter ranged from 0.69 to 1.36 gN/kg of litter integrated over the lifetime of decomposition. Compared to senesced leaf litter, N-fixation during decomposition of non-senesced leaf litter was ∼77% and stalk material ∼140% per unit mass. Peak rates of N fixation occurred between 200 and 400 days of decomposition, and ranged from 1.37 to 3.27 gN/kg/yr. Our empirical results were extrapolated to represent the traditional Hawaiian cropping system; we calculated N-fixation inputs of 4.8–39.0 kgN/ha/yr, with fixed N adding 17–40% of the amount of N added through litter. Findings indicate that significant N may be introduced into natural cropping systems through mulching practices and that small changes in practices greatly alter the total inputs. The use of mulch was likely an important source of N in pre-industrial settings and may be used in contemporary systems to reduce nitrogen fertilizer requirements.